1977
DOI: 10.3382/ps.0561641
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Calcium Supplement Particle Size and Source on the Performance of Laying Chickens

Abstract: A 3 X 3 X 2 factorial arrangement was employed to test three calcium supplements (oyster shell, limestone and a mined marine source) and three dietary calcium levels (1.75, 2.50, and 3.25%) as completely ground material or as 1/3 ground plus 2/3 hen-size material in cage layer diets. Egg production, feed consumption, feed efficiency, egg weight and egg shell strength were not significantly affected by the source of calcium. Performance was improved with increasing dietary calcium levels. Egg production, feed e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
1
2

Year Published

1981
1981
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 7 publications
1
5
1
2
Order By: Relevance
“…In contrast to our findings, former studies concerning OSM supplementation showed beneficial effects on eggshell breakage strength (Watkins et al, 1977;Brister et al, 1981;Makled & Charles, 1987;Proudfoot & Hulan, 1987;Guinotte & Nys, 1991;Grizzle et al, 1992;Ahmad & Balander, 2004). The results of the present study further support some recent investigations by Lichovnikova (2007) and Safaa et al (2008) who observed that oyster shell is less soluble than fine or coarse limestone, contradicting conventional theories of higher digestibility and retention associated with oyster shell by some researchers (Scott et al, 1971;Roland, 1988).…”
Section: Resultscontrasting
confidence: 56%
See 1 more Smart Citation
“…In contrast to our findings, former studies concerning OSM supplementation showed beneficial effects on eggshell breakage strength (Watkins et al, 1977;Brister et al, 1981;Makled & Charles, 1987;Proudfoot & Hulan, 1987;Guinotte & Nys, 1991;Grizzle et al, 1992;Ahmad & Balander, 2004). The results of the present study further support some recent investigations by Lichovnikova (2007) and Safaa et al (2008) who observed that oyster shell is less soluble than fine or coarse limestone, contradicting conventional theories of higher digestibility and retention associated with oyster shell by some researchers (Scott et al, 1971;Roland, 1988).…”
Section: Resultscontrasting
confidence: 56%
“…It was hypothesized that the reason for this was that the larger particles of oyster shells took longer to digest because they remained in the gizzard and were slowly dissolved over a prolonged period (Scott et al, 1971). Confirming this hypothesis, a great deal of previous scientific work reported that oyster shell meal (OSM) supplementation to the layer hen diet significantly improved egg breaking strength (Hauser & Norris, 1946;Watkins et al, 1977;Keshevarz & McCormick, 1991) and egg specific gravity (Makled & Charles, 1987;Grizzle et al, 1992) when compared to limestone.…”
Section: Introductionmentioning
confidence: 66%
“…A diminuição no consumo de ração no menor nível de cálcio contraria os resultados encontrados por Watkins et al (1977), Roland et al (1978Roland et al ( , 1986, Teixeira (1982), Keshavarz (1986) e Rodrigues (1995), nos quais o menor consumo de ração ocorreu com níveis dietéticos de cálcio mais elevados, o que provavelmente pode ter ocorrido devido a outros fatores, tais como o nível de magnésio e o aumento do carbonato, interferindo, assim, na palatabilidade da ração.…”
Section: Resultados E D Resultados E D Resultados E D Resultados E Diunclassified
“…Essa pior conversão alimentar está aliada a uma menor taxa de produtividade dessas aves, uma vez que o cálcio fornecido, provavelmente, não foi suficiente para que as aves apresentassem uma boa produção de ovos. Esses resultados assemelham-se aos obtidos por Watkins et al (1977) e Oliveira (1995) e diferem dos resultados obtidos por Brister et al (1981), Teixeira (1982) O peso médio dos ovos e a unidade Haugh não foram afetados (p>0,05) pelos níveis de cálcio utilizados nos períodos de repouso ou postura. Diferentes níveis de cálcio também não afetaram o peso dos ovos nos trabalhos de Clunies et al (1992a), Keshavarz e Nakajima (1993), Rodrigues (1995) e Oliveira et al (1997.…”
Section: Resultados E D Resultados E D Resultados E D Resultados E Diunclassified
“…Various calcium sources, in both the pulverized and granulated form, have been examined for subsequent egg shell formation. Scott et al (1971), Miller and Sunde (1975), Watkins et al (1977), and Kuhl et al (1977) all reported that the substitution of large particle calcium for a portion of the pulverized supplemental calcium improved egg shell strength. Roland et al (1974) in three short 6-week studies and Muir et al (1975) in a 50-week study utilizing low producing laying hens (67% production) concluded that the large particles of calcium carbonate had no influence on egg shell quality if the birds were receiving adequate calcium.…”
Section: Introductionmentioning
confidence: 94%